Acid dissolution methods for heavy metals determination in pine needles - Poykio, R.; Peramaki, P.
Microwave digestion procedures using HNO3, HNO3+H2O2, HNO3+HClO4, HF mixtures and dry ashing with HF were investigated for heavy metals analysis by either inductively coupled plasma-optical emission spectroscopy (ICP-OES)or ICP-mass spectrometry (ICP-MS)in pine needles. The HF digestion procedures gave about 1.5 times higher values than a mixture of HNO3+H2O2 alone. For Ti determination in needles, the HF procedure using dry ashing is thus recommended. The mean concentrations amounted to 900 mg/kg for Fe and 21.8 mg/kg for Ti in needles collected at an area polluted by a stainless steel works. Those concentrations were 10.6 and 4.3 times higher than in needles collected at an area nearby a pulp mill complex (84.5 mg/kg Fe and 5.0 mg/kg Ti).
Keywords: PINE NEEDLES; DISSOLUTION; PULP AND PAPER MILLS; FERROCHROME AND STAINLESS STEEL WORKS